Co-delivery system of chemotherapy drugs and active ingredients from natural plants: a brief overview of preclinical research for cancer treatment. (3rd May 2020) - Guo, Pu; He, Yingmeng; Xu, Ting; Pi, Chao; Jiang, Qingsheng; Wei, Yumeng; Zhao, Ling
ABSTRACT: Introduction: Many active ingredients from natural plants (AINPs) have been revealed to possess remarkable anticancer properties. Combination chemotherapy of chemo-drugs and AINPs has also proven to be more advantageous than individual chemo-drug treatment with respect to enhancing efficiency, alleviating toxicity, and controlling the development of multidrug resistance (MDR). Co-delivery is considered a promising method to effectively achieve and manage combination chemotherapy of chemo-drugs and AINPs, and various distinctive and functional co-delivery systems have been designed for these purposes to date. Areas covered: This review focuses on recent preclinical investigations of co-delivery systems for chemo-drugs and AINPs as new cancer treatment modalities. We particularly emphasize the apparent treatment advantages of these approaches, including augmenting efficiency, reducing toxicity, and controlling MDR. Expert opinion: There has already been notable progress in the application of combination chemotherapy with co-delivery systems loaded with chemo-drugs and AINPs based on results with cellular and animal models. The main challenge is to translate these successes into new anticancer compound preparations and promote their clinical application in practice. Nevertheless, continuous efforts with new designs of co-delivery systems remain essential, providing a foundation for future clinical research and development of new anticancer drugs.